High-hardness microcrystalline glass and preparation process thereof

By reasonably combining the main components and adding appropriate amounts of substances, combining the synergistic composite and strengthening treatment, the shortcomings of microcrystalline glass in high hardness, corrosion resistance, acid and alkali resistance and heat resistance are solved, and high-performance microcrystalline glass is achieved Preparation of glass.

CN119461853APending Publication Date: 2025-02-18CHANGSHU JIAHE DISPLAY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411723320.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-06
Filing Date
2024-11-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing microcrystalline glasses have shortcomings in high hardness, corrosion resistance, acid and alkali resistance and heat resistance, which are difficult to meet the demand for high-performance microcrystalline glasses in different industries.

Method used

By reasonably combining the main components such as SiO2, Al2O3, Li2O, and adding substances such as P2O5, ZrO2, MgO, etc., the nucleation barrier is reduced and nucleation and crystallization are promoted. At the same time, the integrated composite of iridium oxide, tourmaline and coal-to-oil residue is added to improve the nucleation effect and stability, and the physical and chemical properties of the glass are improved through strengthening treatment.

Benefits of technology

It has achieved high hardness, excellent mechanical properties, good corrosion resistance, acid and alkali resistance and heat resistance of microcrystalline glass, meeting the demand for high-performance microcrystalline glass in different industries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of glass ceramics, and particularly relates to high-hardness microcrystalline glass and a preparation process thereof. The invention discloses high-hardness glass ceramic, which is prepared from the following ingredients in mole fraction: 69 to 69.1 percent of SiO2, 4 to 4.05 percent of Al2O3, 1 to 1.02 percent of P2O5, 22.15 to 22.16 percent of Li2O, 0.07 percent of Na2O, 0.07 percent of K2O, 2.78 to 2.8 percent of ZrO2, 0 to 0.7 percent of MgO, 0 to 0.71 percent of CaO, 0 to 0.72 percent of SrO, 0 to 0.7 percent of BaO, 0 to 0.08 percent of Sb2O3 and the balance of synergistic compounds. Through reasonable compatibility of the raw material components and contents, the obtained microcrystalline glass has high hardness and excellent mechanical properties, and can meet the requirements of different industries on high hardness, wear resistance and corrosion resistance of the microcrystalline glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of glass ceramics, and in particular, relates to a high-hardness microcrystalline glass and a preparation process thereof. Background Art

[0002] Glass-ceramics, also known as glass ceramics and microcrystalline ceramics, is a polycrystalline solid phase material containing a glass body that is obtained by controlled nucleation and crystallization of certain basic glasses of specific composition at a certain temperature. The performance of glass-ceramics is mainly determined by the main crystal phase, which can be achieved by controlling nucleation, crystallization and selecting different mother glass components. Glass-ceramics has the characteristics of both glass and ceramics, with the advantages of high strength, good wear resistance and strong corrosion resistance. It is superior to metals and polymers in thermal, chemical, biological, optical and electrical properties, and can be widely used in building materials and corrosion-resistant or wear-resistant fields such as pipelines, pumps, and bearings.

[0003] Glass-ceramics are divided into silicate glass-ceramics, aluminosilicate glass-ceramics, fluorosilicate glass-ceramics, borate glass-ceramics and phosphate glass-ceramics according to the glass system. Among them, aluminosilicate glass-ceramics has become a research hotspot due to its obvious performance advantages. There are four main systems of aluminosilicate glass-ceramics: Li2O-Al2O3-SiO2 system, MgO-A12O3-SiO2 system, Na2O-Al2O3-SiO2 system, and ZnO-Al2O3-SiO2 system. Among them, Li2O-Al2O3-SiO2 (LAS) glass-ceramics have the characteristics of high strength, low thermal expansion coefficient and stable chemical properties. It is an important type of aluminosilicate glass-ceramics. In the preparation process of LAS glass-ceramics, the composition of the base glass is the key factor that determines the type of precipitated crystal phase and the crystallization ability, which can affect the performance of the material in terms of internal structure. To this end, it is very necessary to select a suitable substance as the main crystalline phase of the microcrystalline glass so that the obtained microcrystalline glass has high deformation resistance, hardness, corrosion resistance, acid and alkali resistance and heat resistance. Summary of the invention

[0004] The primary purpose of the present invention is to provide a high-hardness microcrystalline glass and a preparation process thereof, so as to achieve the high hardness, corrosion resistance, acid and alkali resistance and heat resistance of the obtained microcrystalline glass.

[0005] To this end, the present invention provides the following technical solutions.

[0006] One aspect of the present invention provides a high-hardness microcrystalline glass. The raw materials of the microcrystalline glass include, by mole fraction, SiO2 69-69.1%, Al2O3 4-4.05%, P2O5 1-1.02%, Li2O 22.15-22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.78-2.8%, MgO 0-0.7%, CaO 0-0.71%, SrO 0-0.72%, BaO 0-0.7%, Sb2O30-0.08%, and the remainder of a synergistic compound.

[0007] In a preferred embodiment of the present invention, the raw materials of the microcrystalline glass include, by mole fraction: SiO2 69.05%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO 0.35%, SrO 0.36%, BaO 0.35%, Sb2O3 0.04%, and the remainder of synergistic compounds.

[0008] In a preferred embodiment of the present invention, the synergistic compound is composed of iridium oxide, tourmaline and coal-to-liquid residue in a mass ratio of 1:10-30:100.

[0009] In a preferred embodiment of the present invention, the method for preparing the synergistic compound comprises the following steps: Iridium oxide, tourmaline and coal-to-liquid residue are placed in an oven to dry to constant weight, then ground with a ball mill, and passed through a 400-mesh sieve to obtain raw material powders; Under an inert atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder are uniformly mixed and then placed in a muffle furnace for melting. After the heat preservation is completed, the mixture is cooled to room temperature, and then the obtained product is crushed, ground and mixed to obtain the synergistic composite.

[0010] In a preferred embodiment of the present invention, the iridium oxide powder, tourmaline powder and coal-to-oil residue powder are mixed in a mass ratio of 1:10-30:100.

[0011] In a preferred embodiment of the present invention, the tourmaline is selected from any one of ferro-tourmaline, ferromagnesian tourmaline and black tourmaline.

[0012] In a preferred embodiment of the present invention, the microcrystalline glass satisfies: central tensile stress density>350MPa, 80-grit sandpaper drop>180cm, high temperature and high humidity failure time>240h, CS50 / |CT_CV|>1.05, wherein CS50 refers to the stress value corresponding to a depth of 50µm, and |CT-CV| refers to the absolute value of the maximum tensile stress in the tensile stress layer.

[0013] Another aspect of the present invention provides a method for preparing the high-hardness glass-ceramics as described above, the method comprising the following steps: Weighing raw materials according to the components, mixing the raw material components and then melting them, and placing them in a mold to form a microcrystalline glass embryo; heat-treating the glass-ceramics embryo to obtain a glass-ceramics precursor; The microcrystalline glass precursor is subjected to a strengthening treatment to obtain a microcrystalline glass product.

[0014] In a preferred embodiment of the present invention, the melting conditions are: temperature 1500-1800° C., time 6-10 h.

[0015] In a preferred embodiment of the present invention, the heat treatment process is: heating the microcrystalline glass body to a temperature of 550-600°C, keeping it warm for 3-5 hours, and performing nucleation; heating the nucleated glass to a temperature of 700-780°C, keeping it warm for 1-3 hours, and performing crystallization.

[0016] In a preferred embodiment of the present invention, the strengthening treatment conditions are: immersing the microcrystalline glass precursor in a strengthening molten salt and treating it at 400-600° C. for 6-10 hours.

[0017] In a preferred embodiment of the present invention, the strengthening molten salt is composed of: 70-80 g / L potassium nitrate, 20-30 g / L sodium nitrate and 0-0.05 g / L lithium nitrate.

[0018] In a preferred embodiment of the present invention, the strengthening molten salt is composed of: 70-80 g / L potassium nitrate, 20-30 g / L sodium nitrate, 0-0.05 g / L lithium nitrate, and 10-20 g / L modified silicon dioxide.

[0019] In a preferred embodiment of the present invention, the modified silicon dioxide is prepared according to the following method: Dissolving cyclodextrin in water, and adding acid to adjust the pH value of the solution to 2-4, to obtain an acidic cyclodextrin solution; Add silicon dioxide to the obtained acidic cyclodextrin solution in an amount of 1 g: 10-30 mL by mass volume ratio, heat to 65-75° C., add silane coupling agent under stirring conditions, continue stirring and react for 2-4 hours after the addition is completed, and cool to room temperature after the reaction is completed to obtain modified silicon dioxide.

[0020] In a preferred embodiment of the present invention, the cyclodextrin is mixed with water in a mass ratio of 1-5:100.

[0021] In a preferred embodiment of the present invention, the acid is selected from any one of acetic acid, citric acid, oxalic acid or tartaric acid.

[0022] In a preferred embodiment of the present invention, the silane coupling agent is 3-glycidyloxypropyltrimethoxysilane or 3-glycidyloxypropyltriethoxysilane.

[0023] In a preferred embodiment of the present invention, the added amount of the silane coupling agent is 1-3% of the mass of silicon dioxide.

[0024] By means of the above technical solution, the present invention has at least the following advantages: 1. The present invention makes reasonable combinations of the raw material components and their contents, so that the obtained microcrystalline glass has high hardness and excellent mechanical properties, which can meet the requirements of different industries for high hardness, wear resistance and corrosion resistance of microcrystalline glass. The microcrystalline glass of the present invention has SiO2, Al2O3 and Li2O as main components, and can play a synergistic role by adding substances such as phosphorus pentoxide, sodium oxide, potassium oxide, etc. The addition of these substances can reduce the nucleation barrier, promote nucleation and crystallization, and improve the crystallization performance of the glass.

[0025] 2. The present invention also adds a synergistic compound to the raw material, wherein the synergistic compound is formed by composite melting of iridium oxide, tourmaline and coal-to-oil residue in a certain proportion. Iridium oxide is a brown quadrangular crystal, and its lattice is a rutile structure, wherein there are six-coordinated iridium and three-coordinated oxygen, and its stability is high. The addition of iridium oxide can not only improve the nucleation effect, but also act as a stabilizer. Coal-to-oil residue and tourmaline are both substances containing a large amount of metal oxides. By melting and compounding the three substances, not only can the resource utilization of coal-to-oil residue be realized, but also the hardness and mechanical properties of the product can be provided.

[0026] 3. The present invention also further improves the central tensile stress density and high-temperature high-efficiency failure time of the obtained microcrystalline glass by strengthening the microcrystalline glass, so that the obtained microcrystalline glass has excellent physical and chemical properties.

[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0029] Example 1

[0030] The present embodiment provides a microcrystalline glass, whose raw materials and contents are, by mole fraction, SiO2 69.05%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO0.35%, SrO 0.36%, BaO 0.35%, Sb2O3 0.04%, and the remainder of a synergistic compound.

[0031] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue are placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under a nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder are mixed uniformly in a mass ratio of 1:20:100, then placed in a muffle furnace and melted at 1500-1600°C, kept warm for 30 minutes, and then cooled to room temperature, and then the obtained product is crushed, ground and obtained to obtain the synergistic composite.

[0032] Preparation of microcrystalline glass: weigh the raw materials according to the amount, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0033] Example 2

[0034] The present embodiment provides a microcrystalline glass, whose components and contents, by mole fraction, are: SiO2 69.07%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.78%, CaO 0.71%, Sb2O3 0.07%, and the remainder of a synergistic compound.

[0035] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, ferromagnesian tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, ferromagnesian tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:10:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0036] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1800°C for 6 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to 600°C and kept warm for 3 hours for nucleation; then the nucleated glass is heated to 700°C and kept warm for 3 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 80g / L potassium nitrate, 20g / L sodium nitrate, 0.05g / L lithium nitrate) and treated at 450°C for 10 hours to obtain a finished microcrystalline glass product.

[0037] Example 3

[0038] The present embodiment provides a microcrystalline glass, whose components and contents, by mole fraction, are: SiO2 69.1%, Al2O3 4%, P2O5 1%, Li2O 22.15%, Na2O 0.07%, K2O 0.07%, ZrO2 2.8%, SrO 0.72%, Sb2O30.08%, and the remainder of a synergistic compound.

[0039] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, ferromagnesian tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, ferromagnesian tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:30:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0040] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1500°C for 10 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 550°C and kept warm for 5 hours for nucleation; then the nucleated glass is heated to a temperature of 780°C and kept warm for 1 hour for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 70g / L potassium nitrate, 30g / L sodium nitrate) and treated at 480°C for 6 hours to obtain a finished microcrystalline glass product.

[0041] Example 4

[0042] The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: SiO2 69.05%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO0.35%, SrO 0.36%, BaO 0.35%, Sb2O3 0.04%, and the remainder of a synergistic compound.

[0043] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0044] Preparation of modified silica: Dissolve cyclodextrin and water in water at a mass ratio of 3:100, and add citric acid to adjust the pH value of the solution to 3 to obtain an acidic cyclodextrin solution. Add silica to the obtained acidic cyclodextrin solution at a mass volume ratio of 1g:20mL, heat to 70°C, add 3-glycidyloxypropyltrimethoxysilane (the amount added is 2% of the mass of silica) under stirring, continue stirring and react for 3h after the addition is completed, and cool to room temperature after the reaction is completed to obtain modified silica.

[0045] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate, 15g / L modified silica) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0046] Example 5

[0047] The present embodiment provides a microcrystalline glass, whose components and contents, by mole fraction, are: SiO2 69.10%, Al2O3 4%, P2O5 1%, Li2O 22.15%, Na2O 0.07%, K2O 0.07%, ZrO2 2.80%, BaO 0.35%, Sb2O30.08%, and the remainder of a synergistic compound.

[0048] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0049] Preparation of modified silica: Dissolve cyclodextrin and water in water at a mass ratio of 1:100, and add citric acid to adjust the pH value of the solution to 4 to obtain an acidic cyclodextrin solution. Add silica to the obtained acidic cyclodextrin solution at a mass volume ratio of 1g:30mL, heat to 75°C, add 3-glycidyloxypropyltriethoxysilane (the amount added is 1% of the mass of silica) under stirring, continue stirring and react for 2h after the addition is completed, and cool to room temperature after the reaction is completed to obtain modified silica.

[0050] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate, 20g / L modified silica) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0051] Example 6

[0052] The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: SiO2 69.1%, Al2O3 4%, P2O5 1%, Li2O 22.15%, Na2O 0.07%, K2O 0.07%, ZrO2 2.8%, SrO 0.15%, BaO 0.6%, Sb2O3 0.02%, and the remainder of a synergistic compound.

[0053] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0054] Preparation of modified silica: Dissolve cyclodextrin and water in water at a mass ratio of 5:100, and add citric acid to adjust the pH value of the solution to 2 to obtain an acidic cyclodextrin solution. Add silica to the obtained acidic cyclodextrin solution at a mass volume ratio of 1g:10mL, heat to 65°C, add 3-glycidyloxypropyltrimethoxysilane (the amount added is 3% of the mass of silica) under stirring, continue stirring and react for 4 hours after the addition is completed, and cool to room temperature after the reaction is completed to obtain modified silica.

[0055] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate, 10g / L modified silica) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0056] Comparative Example 1: The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: SiO2 69.05%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO0.35%, SrO 0.36%, BaO 0.35%, Sb2O3 0.04%, and the remainder of a synergistic compound.

[0057] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0058] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate, 15g / L silicon dioxide) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0059] Comparative Example 2: The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: SiO2 69.05%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO0.35%, SrO 0.36%, BaO 0.35%, Sb2O3 0.04%, and the remainder of a synergistic compound.

[0060] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: ferro tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, ferro tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, they were cooled to room temperature, and then the obtained product was crushed, ground and obtained to obtain the synergistic composite.

[0061] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0062] Comparative Example 3: The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO 0.35%, SrO0.36%, BaO 0.35%, Sb2O3 0.04%, and the balance SiO2.

[0063] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for forming, and cool them to room temperature to prepare a glass-ceramic embryo. The glass-ceramic embryo is heated to 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to 740°C and kept warm for 2 hours for crystallization to prepare a glass-ceramic precursor. The glass-ceramic precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate) and treated at 500°C for 8 hours to obtain a finished glass-ceramic product.

[0064] Comparative Example 4: The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: SiO2 69.05%, Al2O3 4.2%, P2O5 1.05%, Li2O 22.20%, Na2O 0.07%, K2O 0.07%, ZrO2 2.7%, Sb2O3 0.08%, and the balance SiO2.

[0065] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0066] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0067] Comparative Example 5: The present embodiment provides a microcrystalline glass, whose components and contents, measured by mole fraction, are: Al2O3 3.85%, P2O5 0.9%, Li2O 22.05%, Na2O 0.07%, K2O 0.07%, ZrO2 2.9%, MgO 0.75%, CaO 0.80%, SrO0.80%, BaO 0.85%, Sb2O3 0.09%, and the balance SiO2.

[0068] This embodiment provides a method for preparing microcrystalline glass, comprising the following steps: Preparation of synergistic composite: iridium oxide, tourmaline and coal-to-oil residue were placed in an oven at 105°C and dried to constant weight, then ground in a ball mill, and passed through a 400-mesh sieve to obtain raw material powders. Under nitrogen atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder were mixed uniformly in a mass ratio of 1:20:100 and then placed in a muffle furnace for melting. After keeping warm for 30 minutes, the mixture was cooled to room temperature, and the obtained product was crushed, ground and mixed to obtain the synergistic composite.

[0069] Preparation of microcrystalline glass: weigh the raw materials according to the components, mix the raw material components, melt them at 1600°C for 7 hours, place them in a mold for molding, and cool them to room temperature to prepare a microcrystalline glass embryo. The microcrystalline glass embryo is heated to a temperature of 580°C and kept warm for 4 hours for nucleation; then the nucleated glass is heated to a temperature of 740°C and kept warm for 2 hours for crystallization to prepare a microcrystalline glass precursor. The microcrystalline glass precursor is immersed in a strengthening molten salt (composed of: 75g / L potassium nitrate, 25g / L sodium nitrate, 0.03g / L lithium nitrate) and treated at 500°C for 8 hours to obtain a finished microcrystalline glass product.

[0070] Experiment 1: Comparison of physical properties of different glass-ceramics Experimental objects: Examples 1-6 and Comparative Examples 1-5 Experimental methods: 1) Central tensile stress density detection: Use Japan Orihara stress meter SLP-2000 (518nm) for testing. Test conditions: light source wavelength 518nm, SOC = 25.5 (nm / cm) / MPa, refractive index = 1.56, exposure time: 150usec.

[0071] 2) 80-grit sandpaper drop test: The drop value of sandpaper is used to characterize the drop resistance of glass. A drop test machine is used to perform a surface drop test on the glass sample using 80-grit silicon carbide sandpaper (Eagle brand sandpaper) to evaluate its drop resistance. The test conditions are: 80-grit sandpaper, 210g total weight (refers to the total mass of the chemically strengthened glass plus the mobile phone model, which is equivalent to a 210g mobile phone with a chemically strengthened glass plate falling down), 30cm base height, 10cm increment, 1 drop at each height until the glass breaks, and the broken height is recorded.

[0072] CS-50 / |CT_CV|: CS-50 refers to the stress value corresponding to a depth of 50µm; |CT-CV| refers to the absolute value of the maximum tensile stress in the tensile stress layer.

[0073] Test method for failure time under high temperature and high humidity: Use QTH_80C full temperature and humidity alternating test chamber for testing, and the alternating test chamber conditions are set as follows: temperature is 85℃ and relative humidity is 85%. Take out the sample every 12 hours for observation, and continue for 10 days. Visually inspect the sample in a light box (light source intensity 1000-1200Lux), and wipe the glass surface with a dust-free cloth to observe whether there are spots or fog points that cannot be wiped off.

[0074] Experimental results: see Table 1 (t=0.6mm).

[0075] Table 1 Physical properties of glass-ceramics Group Central tensile stress density (MPa / mm) CS50 / CT_CV 80-grit sandpaper drop (cm) High temperature and high humidity failure time (h) <![CDATA[Vickers hardness (kgf / mm 2 ).]]> DOL stress layer depth (μm) Example 1 292 0.93 170 240 860 125 Example 2 283 0.91 160 240 874 121 Example 3 306 0.94 170 228 865 128 Example 4 316 0.92 180 250 880 136 Example 5 314 0.96 190 258 895 141 Example 6 313 0.91 170 245 872 130 Comparative Example 1 256 0.97 160 204 839 124 Comparative Example 2 238 0.98 130 192 804 112 Comparative Example 3 236 0.90 120 216 752 101 Comparative Example 4 270 0.94 140 214 845 116 Comparative Example 5 275 0.91 150 210 843 118 From the results in Table 1, it can be seen that compared with comparative examples 1-5, the physical properties of the microcrystalline glass of Examples 1-6 of the present invention are better, which shows that the performance of the microcrystalline glass can be significantly improved by adding a synergistic compound, wherein the addition of iridium oxide can play the role of a synergistic compound with tourmaline and coal-to-oil residue, so that the final microcrystalline glass has better performance. Compared with Examples 1-3, the central tensile stress density, 80-grit sandpaper drop, etc. of Examples 4-6 are better than those of Examples 1-3, which shows that the physical properties of the microcrystalline glass can be significantly improved by improving the strengthening liquid, especially by adding modified silica to the strengthening liquid.

[0076] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A high-hardness glass-ceramic, characterized in that: Calculated by mole fraction, the raw materials of the microcrystalline glass include: SiO2 69-69.1%, Al2O3 4-4.05%, P2O5 1-1.02%, Li2O 22.15-22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.78-2.8%, MgO 0-0.7%, CaO 0-0.71%, SrO 0-0.72%, BaO 0-0.7%, Sb2O3 0-0.08%, and the balance of synergistic compounds.

2. The high-hardness glass-ceramics according to claim 1, characterized in that: Calculated by mole fraction, the raw materials of the microcrystalline glass include: SiO2 69.05%, Al2O3 4.05%, P2O5 1.01%, Li2O 22.16%, Na2O 0.07%, K2O 0.07%, ZrO2 2.79%, MgO 0.35%, CaO 0.35%, SrO 0.36%, BaO 0.35%, Sb2O3 0.04%, and the balance of synergistic compounds.

3. The high-hardness microcrystalline glass according to claim 1 or 2, characterized in that: The preparation method of the synergistic composite comprises the following steps: Iridium oxide, tourmaline and coal-to-liquid residue are placed in an oven to dry to constant weight, then ground with a ball mill, and passed through a 400-mesh sieve to obtain raw material powders; Under an inert atmosphere, iridium oxide powder, tourmaline powder and coal-to-oil residue powder are uniformly mixed and then placed in a muffle furnace for melting. After the heat preservation is completed, the mixture is cooled to room temperature, and then the obtained product is crushed, ground and mixed to obtain the synergistic composite.

4. The high-hardness glass-ceramics according to claim 3, characterized in that: The iridium oxide powder, tourmaline powder and coal-to-oil residue powder are mixed in a mass ratio of 1:10-30:

100.

5. The high-hardness glass-ceramics according to claim 3, characterized in that: The tourmaline is selected from any one of iron tourmaline, ferromagnesian tourmaline and black tourmaline.

6. A method for preparing high-hardness microcrystalline glass according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Weighing raw materials according to the amounts, mixing the raw material components and then melting them, and placing them in a mold to form a microcrystalline glass embryo; heat-treating the glass-ceramics embryo to obtain a glass-ceramics precursor; The microcrystalline glass precursor is subjected to a strengthening treatment to obtain a microcrystalline glass product.

7. The preparation method according to claim 6, characterized in that: The melting conditions are: temperature 1500-1800° C., time 6-10 h.

8. The preparation method according to claim 6, characterized in that: The heat treatment process is as follows: heating the microcrystalline glass body to a temperature of 550-600° C., keeping the temperature for 3-5 hours, and performing nucleation; and heating the nucleated glass to a temperature of 700-780° C., keeping the temperature for 1-3 hours, and performing crystallization.

9. The preparation method according to claim 6, characterized in that: The strengthening treatment conditions are: immersing the microcrystalline glass precursor in strengthening molten salt and treating it at 400-600° C. for 6-10 hours.

10. The preparation method according to claim 9, characterized in that: The strengthening molten salt is composed of 70-80 g / L potassium nitrate, 20-30 g / L sodium nitrate and 0-0.05 g / L lithium nitrate.

Citation Information

Patent Citations

  • Vanadium titano-magnetite tailing glass-ceramic and preparation method thereof

    CN104926131A

  • Foam glass ceramics releasing anions and having far-infrared emission function and preparation method and application thereof

    CN105293907A

  • Glass reinforcing agent and glass reinforcing method

    CN115893871A

  • High-strength microcrystalline glass and preparation method thereof

    CN118084333A

  • Glass frit mixture, method of manufacturing electronic circuit board, and electronic circuit board

    JP2004182510A